Practice-Based Entrepreneurship Training Through Market Validation and Mentoring: A Community Engagement Program at Universitas Sugeng Hartono - Suyahman Suyahman; Deny Prasetyo; Ardy Wicaksono; Dwi Utari Iswavigra; Yulaikha Mar'atullatifah; Ahmad Aufar Ribhi; Muhamad Wisnu Pangestu (Sah Publisher, 2026)
Entrepreneurship courses can become overly centered on concepts and business plans when students have limited contact with customers and market uncertainty. This article describes the implementation of a practice-based entrepreneurship training program for 24 students at Universitas Sugeng Hartono from May 14 to June 25, 2026. The program combined entrepreneurial-mindset orientation, business proposal development, preparation of marketing materials, direct market practice, weekly progress reporting, mentoring, and final reflection. A descriptive qualitative approach was used to organize evidence from proposals, progress reports, classroom observations, supporting documentation, and student reflections. The implementation produced a structured learning sequence that moved from opportunity identification to customer contact, feedback, and strategy revision. Market validation and minimum viable product concepts gave students a practical basis for testing assumptions before expanding a business idea. Weekly reports made activity, obstacles, and follow-up decisions visible, while mentoring sessions converted individual difficulties into shared problem-solving material. Because participant records were heterogeneous and did not provide a complete standardized outcome dataset, the program cannot support claims about causal effects, average revenue gains, or changes in entrepreneurial intention. Its contribution is an implementable model for connecting entrepreneurship concepts with customer-facing action and reflective mentoring. Future delivery should retain the practice cycle while adding common indicators, baseline and endline measures, and systematic reflection records